1999
DOI: 10.1046/j.1365-2958.1999.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Protonmotive force, ExbB and ligand‐bound FepA drive conformational changes in TonB

Abstract: SummaryTonB couples the cytoplasmic membrane protonmotive force (pmf) to active transport across the outer membrane, potentially through a series of conformational changes. Previous studies of a TonB transmembrane domain mutant (TonB-⌬V17) and its phenotypical suppressor (ExbB-A39E) suggested that TonB is conformationally sensitive. Here, two new mutations of the conserved TonB transmembrane domain SHLS motif were isolated, TonB-S16L and -H20Y, as were two new suppressors, ExbB-V35E and -V36D. Each suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
275
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(291 citation statements)
references
References 63 publications
14
275
2
Order By: Relevance
“…Upon sensing of proton motive force (pmf) through partner protein interactions at the IM, TonB undergoes a structural transition as monitored by a change in protease susceptibility (19). Similarly, we found that VirB10 adopts alternative protease-susceptible and -resistant conformations as a function of cellular energetic status.…”
Section: Virb10 Protease Susceptibility As a Function Of Cellular Atpmentioning
confidence: 82%
See 2 more Smart Citations
“…Upon sensing of proton motive force (pmf) through partner protein interactions at the IM, TonB undergoes a structural transition as monitored by a change in protease susceptibility (19). Similarly, we found that VirB10 adopts alternative protease-susceptible and -resistant conformations as a function of cellular energetic status.…”
Section: Virb10 Protease Susceptibility As a Function Of Cellular Atpmentioning
confidence: 82%
“…Similarly, TonB possesses motifs enabling contacts with its partner proteins at both membranes. For TonB, these transenvelope protein contacts are thought to form simultaneously or through a shuttle mechanism to mediate coupling of IM transmembrane potential to the gating of OM transporters (17)(18)(19)). Thus, we tested whether VirB10 might also contribute to T4SS machine assembly or function through an energy-sensing mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DfepA strain KP1490 was constructed by a FLP recombinaseassisted homologous recombination (Datsenko and Wanner, 2000). Briefly the chromosomal fepA in KP1270 [W3110 aroB ( Larsen et al, 1999)] was replaced by kan r gene, resulting in strain KP1488. The kan r gene was subsequently excised using FLP recombinase, resulting in strain KP1490.…”
Section: Strainsmentioning
confidence: 99%
“…ExbBD proteins are auxiliary partners of TonB protein, which is responsible for the energy-dependent uptake of iron-charged siderophores (15). As for TolA, activity of TonB is dependent upon PMF, ExbB, ExbD, and a conserved motif within the TonB inner membrane anchor, regulating conformational modifications (16,17). MotA and MotB are the two components of the flagellar stator, responsible for coupling PMF with flagella rotation (18).…”
mentioning
confidence: 99%